2015
DOI: 10.1016/j.jneuroim.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of macrophage phenotype by mature and pro-nerve growth factor

Abstract: To characterize the role of neurotrophin receptors on macrophages, we investigated the ability of nerve growth factor (NGF) and its precursor, proNGF, to regulate human macrophage phenotype. The p75 neurotrophin receptor (p75NTR) and TrkA were concentrated within overlapping domains on membrane ruffles. NGF stimulation of macrophages increased membrane ruffling, calcium spiking, phagocytosis and growth factor secretion. In contrast, proNGF induced podosome formation, increased migration, suppressed calcium spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 58 publications
(80 reference statements)
1
51
0
2
Order By: Relevance
“…ProNGF+HIV had no effect on phagocytosis compared to control or HIV-treated cells. This result was counterintuitive since previous studies had shown that a more ruffled phenotype is associated with phagocytic activity (Williams et al 2015). However, in the presence of …”
Section: Hiv Had No Effect On Phagocytic Activity In Hmdmmentioning
confidence: 76%
See 4 more Smart Citations
“…ProNGF+HIV had no effect on phagocytosis compared to control or HIV-treated cells. This result was counterintuitive since previous studies had shown that a more ruffled phenotype is associated with phagocytic activity (Williams et al 2015). However, in the presence of …”
Section: Hiv Had No Effect On Phagocytic Activity In Hmdmmentioning
confidence: 76%
“…The neurotrophin receptors p75 NTR and TrkA have recently been shown to be robustly expressed on hMDM and monocytes (Williams et al 2015). To assess whether HIV could regulate the expression of p75 NTR and TrkA, hMDM were exposed to HIV virions for 1 h followed by flow cytometry analysis.…”
Section: P75 Ntr and Trka Expression In Response To Hivmentioning
confidence: 99%
See 3 more Smart Citations